2020
DOI: 10.1149/1945-7111/ab8a97
|View full text |Cite
|
Sign up to set email alerts
|

Review—Corrosion-Resistant Metastable Al Alloys: An Overview of Corrosion Mechanisms

Abstract: Commercial aluminum alloys exhibit localized corrosion when exposed to environments containing aggressive anions. Alloying of Al with specific elements (M: Cr, Mo, V, Nb, etc) using non-equilibrium processing techniques has been reported to result in significantly improved corrosion resistance due to the formation of a supersaturated solid solution and uniform distribution of M in the matrix. Several theories describing the corrosion behavior of Al–M alloys have been postulated. This paper presents an overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 150 publications
0
18
0
Order By: Relevance
“…The corrosion resistance of the ball-milled Al alloys was high despite a nonuniform microstructure. The improved corrosion resistance of these Al alloys was hypothesized due to one or more of the following mechanisms, which are proposed based on the literature on the sputter-deposited Al alloys, ball-milled alloys Al, and stainless steels 4,[12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion resistance of the ball-milled Al alloys was high despite a nonuniform microstructure. The improved corrosion resistance of these Al alloys was hypothesized due to one or more of the following mechanisms, which are proposed based on the literature on the sputter-deposited Al alloys, ball-milled alloys Al, and stainless steels 4,[12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Different stripping agents such as: (cold water, hot water, 2.0M H2SO4 and 2.0M HNO3) were studied at A/O volume ratio of 1/1 and equilibrium time 5 min. The obtained data in figure (2) revealed that, H2SO4 solution is the most effective agent for Ce stripping with efficiency of 82.2%.…”
Section: Effect Of Stripping Agent Typesmentioning
confidence: 89%
“…Different O/A volume ratios ranging from 1/3 to 3/1 were studied by contacting the nitrate solution with 15% TBP in kerosene at pH of 1.7 and 7min equilibrium time. The obtained data in table (2) emphasized that, although the extraction efficiencies of Ce(IV) increased to 92.1 and 94.9% at O/A ratios of 2/1 and 3/1, respectively; but these ratios were not applied because the loaded Ce(IV) was diluted in the organic phase. On the other hand, the O/A ratios of 1/2 and 1/3 showed lower extraction efficiencies of Ce(IV).…”
Section: Effect Of (O/a) Volume Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been stated that the presence of oxidized species of TMs in the alumina-based surface layer improve the corrosion resistance of Al-TM alloys, aluminides, and Al-based CMAs in chloride solutions and sulfuric acid solutions by blocking the aggressive-ion entry sites in the passive layers [59][60][61] or stabilizing the passive layers [62]. Recently, Esquivel and Gupta [63] summarized the proposed mechanisms for the contribution of TMs in the passivation ability of Al-TM alloys prepared by non-equilibrium processing techniques. Here, it should be noted that the similarity in the i p1 values of the high-Co alloys (10-20 wt.% Co), may be justified by the following reasoning: The increase in i p1 (stage 2) due to the decrease in the passive surface area, i.e., Al matrix, can to some extent counterbalance the decrease in i p1 due to the increase in the dissolved (in the matrix) Co content.…”
Section: Polarization Performance In 1 M H 2 So 4 Versus Co Contentmentioning
confidence: 99%